PENERAPAN SELF LEADERSHIP TERHADAP KINERJA PERAWAT: KAJIAN LITERATUR [THE APPLICATION OF SELF-LEADERSHIP TO NURSE PERFORMANCE: A LITERATURE REVIEW] - Lekatompessy, Christika; Wijayanti, Catharina Dwiana (Nursing Current: Jurnal Keperawatan, 2024)
Nurses who provide nursing services require leadership abilities. The concept of leadership is not only owned by a nurse manager but must also be owned by a primary nurse and an implementing nurse when carrying out nursing services. By developing self-leadership, nurses can become more effective leaders, share knowledge and innovation, and face work demands better. This literature review is to determine the impact of applying self-leadership on nurses performances. This study used literature review. The databases used as literature sources consist of Google Scholar, Science Direct, Pubmed, ProQuest, and GaleCencage. Article selection used protocol guidelines (PRISMA) starting from identification, screening, and eligibility, and in the final stage, there were 10 articles analysed. The results of this literature divide three main topics: self-leadership on clinical leadership competency, self leadership on work engagement, and self-leadership can reduce burnout. Self-leadership is a person's who ability to influence, directed, and motivated themself to achieve a goal. Self-leadership can reduce burnout, influence clinical leadership competence, and increase the work engagement of nurses in hospitals. BAHASA INDONESIA Perawat membutuhkan kemampuan kepemimpinan dalam memberikan pelayanan keperawatan. Konsep kepemimpinan tidak terbatas dimiliki oleh seorang perawat manajer namun juga harus dimiliki oleh seorang perawat primer dan perawat pelaksana dalam melaksanakan layanan keperawatan. Dengan memperluas kemampuan self leadership, perawat lebih efektif menjadi seorang pemimpin, berkontribusi dalam berbagi ide kreatif dan inovasi, serta menghadapi tuntutan pekerjan mereka dengan sangat efektif. Literature review ini bertujuan untuk mengetahui pengaruh penerapan self leadership dengan kinerja perawat dalam keperawatan. Penelitian ini menggunakan studi literature review. Database yang digunakan sebagai sumber terdiri dari Google Scholar, Science Direct, Pubmed, ProQuest, Gale Cencage. Penyeleksian artikel menggunakan panduan protocol (PRISMA) mulai dari identification, screening, eligibility dan tahap terakhir terdapat 10 artikel yang dianalisa. Hasil analisis literature menunjukkan bahwa terdapat 3 topik besar yaitu: Self-Leadership terhadap kompetensi kepemimpinan klinis, Self-Leadership terhadap keterlibatan kerja dan Self-Leadership dapat mengurangi burnout. Self-leadership atau Self leadership adalah kemampuan seseorang dalam mempengaruhi, mengarahkan dan memotivasi dirinya dalam mencapai suatu tujuan. Self leadership dapat mengurangi burnout, mempengaruhi kompetensi kepemimpinan klinis dan meningkatkan keterlibatan kerja di Rumah sakit.